A study on membership overlap among different NGOs in selected villages: its impact on micro-credit programmes and rural poor - Chaudhury, Iftekhar A. (BRAC, 2019)
For several decades BRAC and many other NGOs have been working with micro credit for alleviating rural poverty. The growth of micro credit has therefore been phenomenal, and so has the number of smaller NGOs working along this line. According to one estimate, Grameen Bank together with other NGOs account for 65 percent of total rural credit disbursement annually, a figure surpassing the combined total of GOs and Banks. The present study looked into the phenomenon of membership overlapping in some villages of Tangail. The study was exploratory in nature and the findings suggest that a majority of the sample borrowers have benefited from multiple borrowings, while others have not been so successful and some even ended up as paupers. Incidence of membership overlapping is high and its prevalence is likely to be found in other parts of the country as well. These have wide ranging implications for the provider of funds. The objective of the study has been to identify the nature and causes of the incidence of membership overlap between different NGOs in selected villages and evaluate its impact on micro-credit programmes and rural poor. The database for the present study came from field level investigations which were conducted in 10 BRAC village organizations (VOs) under three thanas of Tangail. Out of a total of 326 members in the 10 VOs, Focus Group Discussions were held with 115 members. In-depth interviews of 39 multiple members along with nine case studies were taken from this sample. Besides BRAC, these borrowers also have membership in several other NGOs such as Grameen Bank, Proshika, ASA, Society for Social Services (SSS), Social Development Sangshad (SDS), Swanirvar Bangladesh and BURO Tangail. The major findings of the study indicate that: There is a high incidence of membership overlap. Its prevalence has been found to be very widespread in the study area. A majority of the multiple borrowers are landless, illiterate and enjoy relatively good networking privileges. The motivating factor, behind membership overlapping, revolves around the inadequacy of loans obtained from their parent organization to meet one or any combination of the following categories of loans: (i) credit required to carry on and expand agriculture, cottage industry and business (ii) credit needed to meet long standing problems such as house construction or repair or meet social obligations such as marriage, etc. (iii) credit needed to cope crisis such as unemployment, accident, etc. Data show that 69.73 percent of the loan has been utilized by the multiple borrowers for productive uses and 30.27 percent for unproductive uses. The end use of the loan have been traced to housing (5.40 percent), purchase of cow (6.30 percent), marriage (5.19 percent), medical treatment due to sickness/accident (3.20 percent) and paying loan installment of another NGO ( 4.04 percent). Two percent of the loan has been used for relending at an exorbitant rate of interest. The study found repayment performance of the major multiple borrowers to be regular. Out of a total of 326 borrowers, 210 (64.42 percent) have been regular in repaying loan installments, 63 ( 19.33 percent) have been irregular and 53 ( 16.26 percent) defaulted.